Corporate Social Responsibility (CSR) Activities at PT XYZ - Suhardianto; Sudrajat, Denny; sudirman (International Publisher, 2023)
This study aims to determine the extent to which the implementation of corporate social responsibility/CSR is carried out by PT. XYZ Indonesia is carried out in accordance with applicable regulations and to find out the effect of implementing these Corporate Social Responsibility activities. The method used in this study is observation by collecting data obtained through interviews with the company and the community and paying attention to the supporting literature. The data obtained were then analyzed qualitatively and presented in detail descriptive by the author. Based on the results of the research and the data obtained, it can be concluded that the CSR activities carried out by PT. XYZ Indonesia in the form of compensation for orphans and slaughter of sacrificial animals which aims to build a positive image and create an image that the company pays attention to the condition of the surrounding community. There are several obstacles faced by the company in carrying out this CSR activity, namely a lot of data that is not in accordance with the database that has been made by the committee, and the difficulty of managing the people who come. However, these obstacles can be overcome with various solutions carried out by the organizers such as coordinating with the local RT/RW and creating a coupon exchange system that has been made before.